The good enough therapist : futility, failure, and forgiveness in treatment - Sachs, Brad, 1956- (New York : Routledge, 2020)
"The Good Enough Therapist is a guidebook-not an instruction manual-written for beginning, intermediate and experienced clinicians. It encourages readers to explore, accept, and embrace their flaws and failings in a way that promotes effective treatment as well as personal growth. It focuses both on craft and process-craft related to the tools, the strategies, and the tactics of treatment, process related to the session-by-session struggle to implement these tools in ways that speak to and illuminate the experiencing of living and struggling as a human being"--
OCLC-licensed vendor bibliographic record.
Keywords: Psychotherapy; Psychotherapist and patient; PSYCHOLOGY / Psychotherapy / Counseling; PSYCHOLOGY / Psychotherapy / General; PSYCHOLOGY / Mental Health